2013
DOI: 10.1002/pola.26642
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy functionalized polymethacrylates based on various multifunctional d‐glucopyranoside acetals

Abstract: The synthesis of acetal‐derived d‐glucopyranosides with a various number of hydroxyl groups (the first step, acetalization) and their modified forms with bromoester groups (the second step, esterification) are presented here. The latter, due to the type of functional groups, can be used to initiate the controlled atom transfer radical polymerization. The copolymerizations of equimolar feed of methacrylate monomers, namely, methyl methacrylate and glycidyl methacrylate, were initiated by prepared new glycoiniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…It has previously been reported that this protection reaction has been achieved through one‐step processes 728. However, these transformations require high temperature,7 extended reaction times,815 metal catalysts1627 or stoichiometric catalysis 28. Recently, the organocatalytic synthesis of 4,6‐benzylidene glycosides from aromatic aldehydes in one step under mild conditions was reported by Schmidt and co‐workers 29.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that this protection reaction has been achieved through one‐step processes 728. However, these transformations require high temperature,7 extended reaction times,815 metal catalysts1627 or stoichiometric catalysis 28. Recently, the organocatalytic synthesis of 4,6‐benzylidene glycosides from aromatic aldehydes in one step under mild conditions was reported by Schmidt and co‐workers 29.…”
Section: Introductionmentioning
confidence: 99%
“…The levorotary derivatives of d ‐(−)‐salicin (2‐(hydroxymethyl)phenyl‐β‐D‐glucopyranoside) ( I and II ) were prepared in two steps . The condensation of salicin with SLA or TPhA yielded the products with OCHO group(s) at C‐4 and C‐6 (C‐4′and C‐6′) corresponding to unsymetrical monoacetal, and symmetrical diacetal, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of methyl α-D-glucopyranoside-based initiators (GI1, GI2, GI3) ATRP sugar initiators based on methyl α-D-glucopyranoside were prepared according to previously described procedures [26]. The condensation of MeαDGlu and BZA (1:2) or SLA (1:4) or TPhA (2:1) in a benzene/DMF containing catalyst pTSA (0.2 g for GI1; 0.4 g for GI2 and GI3) was performed in argon with stirring, and then water was removed by a DeanStark apparatus, whereas the catalyst was deactivated with CaCO 3 , and filtered off.…”
Section: Methodsmentioning
confidence: 99%
“…The initiators (GI1-GI3) based on the acetal derivatives of methyl α-D-glucopyranoside with 2-bromoisobutyryl groups (f Br =2-4, Scheme 1), which are optically active and therefore indicating positive values of the specific rotation ([α] D =+32°− +44°), were applied [26]. They were prepared in a two-step procedure, that is i) the condensation of methyl α-Dglucopyranoside with benzaldehyde, salicylaldehyde, and terephthalaldehyde catalyzed by p-toluenesulfonic acid, and ii) the esterification of secondary hydroxyl groups by 2-bromoisobutyryl bromide.…”
Section: Sugar-based Copolymers With Oxirane Pendant Groupsmentioning
confidence: 99%
See 1 more Smart Citation